2021
DOI: 10.1108/mf-07-2021-0327
|View full text |Cite
|
Sign up to set email alerts
|

What drives working adults to be better prepared for their retirements?

Abstract: PurposeThis study aims to understand the drivers that help working adults to be better prepared for retirement, by examining the relationship between financial literacy (FL), financial attitude (FA), financial well-being (FWB), financial behavior (FB) and retirement preparation (RP). RP includes multidimensional measures, which are retirement confidence, retirement planning, long-term financial planning and private retirement schemes (PRS) participation.Design/methodology/approachThis was a quantitative study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Retirement preparation [10] is a form of acceptance, alert-ness, and willingness by individuals due to changes that are no longer working, manifested in the form of behaviour. According to [11] those who have retired but participate in certain activities or continue to work can reap a variety of benefits, including the ability to live a longer, healthier, and more prosperous retirement than those who have retired but have no substitute job or activity.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Retirement preparation [10] is a form of acceptance, alert-ness, and willingness by individuals due to changes that are no longer working, manifested in the form of behaviour. According to [11] those who have retired but participate in certain activities or continue to work can reap a variety of benefits, including the ability to live a longer, healthier, and more prosperous retirement than those who have retired but have no substitute job or activity.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Furthermore, several authors discuss determinants of retirement planning in addition to financial literacy. Chua and Chin [187] examined the relationship between financial literacy, financial attitude, financial well-being, financial behavior and retirement preparation. The empirical evidence indicated that financial behavior is positively associated with retirement preparation; in addition, they found that financial well-being positively effects retirement confidence.…”
Section: Financial Literacy and Retirement Planningmentioning
confidence: 99%
“…Financially literate individuals better understand financial instruments and their terms, rendering them more adept at making well-informed investment decisions (Grohmann et al, 2018). They exhibit stock market participation intentions (Mirzaei & Buer, 2022), save funds for rainy days (de Bassa Scheresberg, 2013), have their retirement plans in place (Chua & Chin, 2022), and therefore experience comparatively greater financial satisfaction (Sconti, 2022). FL not only enhances personal financial well-being but also improves firm performance (Anwar et al, 2020;Saeed, 2024).…”
Section: Introductionmentioning
confidence: 99%